A prospective study of the impact of fluorodeoxyglucose positron emission tomography with concurrent non‐contrast CT scanning on the management of operable pancreatic and peri‐ampullary cancers. Issue 7 (30th April 2015) - Burge, Matthew E.; O'Rourke, Nick; Cavallucci, David; Bryant, Richard; Francesconi, Alessandra; Houston, Kathleen; Wyld, David; Eastgate, Melissa; Finch, Robert; Hopkins, George; Thomas, Paul; Macfarlane, David
Abstract Background The role of fluorodeoxyglucose (FDG) positron emission tomography (PET/CT) scanning in operable pancreas cancer is unclear. We, therefore, wanted to investigate the impact of PET/CT on management, by incorporating it into routine work‐up. Methods This was a single‐institution prospective study. Patients with suspected and potentially operable pancreas, distal bile duct or ampullary carcinomas underwent PET/CT in addition to routine work‐up. The frequency that PET/CT changed the treatment plan or prompted other investigations was determined. The distribution of standard uptake values (SUV) among primary tumours, and adjacent to biliary stents was characterised. Results Fifty‐six patients were recruited. The surgical plan was abandoned in 9 (16%; 95% CI: 6–26) patients as a result of PET/CT identified metastases. In four patients, metastases were missed and seven were inoperable at surgery, not predicted by PET/CT. Unexpected FDG uptake resulted in seven additional investigations, of which two were useful. Among primary pancreatic cancers, a median SUV was 4.9 (range 2–12.1). SUV was highest around the biliary stent in 17 out of 28 cases. PET/CT detected metastases in five patients whose primary pancreatic tumours demonstrated mild to moderate avidity (SUV < 5). Conclusions PET/CT in potentially operable pancreas cancer has limitations. However, as a result of its ability to detect metastases, PET/CT scanning is a useful tool in the selection of such patients for surgery.